Ramadan Fasting Leads to Shifts in Human Gut Microbiota Structured by Dietary Composition - Ali, Ikram; Liu, Ke; Long, Danfeng; Faisal, Shah; Hilal, Mian Gul; Ali, Izhar; Huang, Xiaodan; Long, Ruijun (Frontiers in Microbiology, 2021)
The structure and diversity of human gut microbiota are directly related to diet, though less is known about the influences of ethnicity and diet-related behaviors, such as fasting (intermittent caloric restriction). In this study, we investigated whether fasting for Ramadan altered the microbiota in Chinese and Pakistani individuals. Using high-throughput 16S rRNA gene sequencing and self-reported dietary intake surveys, we determined that both the microbiota and dietary composition were significantly different with little overlap between ethnic groups. Principal Coordinate Analyses (PCoA) comparison of samples collected from both groups before and after fasting showed partial separation of microbiota related to fasting in the Pakistani group, but not in the Chinese group. Measurement of alpha diversity showed that Ramadan fasting significantly altered the coverage and ACE indices among Chinese subjects, but otherwise incurred no changes among either group. Specifically, Prevotella and Faecalibacterium drove predominance of Bacteroidetes and Firmicutes in the Pakistani group, while Bacteroides (phylum Bacteroidetes) were the most prevalent among Chinese participants both before and after fasting. We observed significant enrichment of some specific taxa and depletion of others in individuals of both populations, suggesting that fasting could affect beta diversity. Notably, Dorea, Klebsiella, and Faecalibacterium were more abundant in the Chinese group after fasting, while Sutterella, Parabacteroides, and Alistipes were significantly enriched after fasting in the Pakistani group. Evaluation of the combined groups showed that genera Coprococcus, Clostridium_XlV, and Lachnospiracea were all significantly decreased after fasting. Analysis of food intake and macronutrient energy sources showed that fat-derived energy was positively associated with Oscillibacter and Prevotella, but negatively associated with Bacteroides. In addition, the consumption of sweets was significantly positively correlated with the prevalence of Akkermansia. Our study indicated that diet was the most significant influence on microbiota, and correlated with ethnic groups, while fasting led to enrichment of specific bacterial taxa in some individuals. Given the dearth of understanding about the impacts of fasting on microbiota, our results provide valuable inroads for future study aimed at novel, personalized, behavior-based treatments targeting specific gut microbes for prevention or treatment of digestive disorders.